2020
DOI: 10.1038/s41598-020-75606-4
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Sex dependent effects of post-natal penicillin on brain, behavior and immune regulation are prevented by concurrent probiotic treatment

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Antibiotics were administered to mice in the early postnatal phase of life in seven articles (16 populations; Table 3 ). Kayyal et al (2020) reported that oral penicillin administration led to a decrease in sociability but not anxiety in male mice without any behavioral changes in female mice 21 days post-antibiotic intake. Orally administered ampicillin and vancomycin alone caused significant increase in anxiety and decrease in social novelty, spatial cognition and sociability (except in ampicillin-treated mice) 14 days after cessation of treatments ( Liu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibiotics were administered to mice in the early postnatal phase of life in seven articles (16 populations; Table 3 ). Kayyal et al (2020) reported that oral penicillin administration led to a decrease in sociability but not anxiety in male mice without any behavioral changes in female mice 21 days post-antibiotic intake. Orally administered ampicillin and vancomycin alone caused significant increase in anxiety and decrease in social novelty, spatial cognition and sociability (except in ampicillin-treated mice) 14 days after cessation of treatments ( Liu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies differed in the dosage of ampicillin used. Gut Firmicutes levels increased after penicillin V administration only in 14 days old male mice, but not in females ( Kayyal et al, 2020 ). Sex-related differences in response to the same antibiotics were also reported by Lynch et al (2023) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation